Organization of the ugid LLC "Korostyshivzeminvest" of the Horodske starostyn district of the Zhytomyr region - Karas, I.; Khudrik, A.; Pitsil, A.; Rudenko, Yu.; Lukhyanenko, O. (Land Management, Cadastre and Land Monitoring, 2025)
According to current legislation, the highest priority among all lands belongs to agricultural lands. This category is extremely important due to the use of land resources to provide society with food. Today, the largest share of land plots is in the private sector, used by individuals and legal entities. Quite often, lands are used contrary to their natural characteristics and intended purpose. As a result, the quality of agricultural lands, their natural fertility, water and wind erosion, etc., significantly decrease. In order to avoid such negative consequences of irrational land use, it is advisable to organize lands based on the justification of design decisions.Land organization was carried out for LLC "Korostyshivzeminvest" of the Gorodsky Starostynsky District of Zhytomyr Region. In general, the territory of the farm is characterized by a temperate continental climate with sufficient moisture supply and optimal temperature indicators. Taking into account the relief of the land use area and the distribution by agricultural subgroups of soils, a five-field field crop rotation was proposed with the following crops: winter wheat; corn, winter rapeseed; spring cereals (barley, wheat); corn; soybeans. The cultivation of these crops is expected to result in a positive humus balance and its growth compared to the pre-project state (+627,7 kg/ha).Keywords: land, improvement, economy, design solution, humus balance.